Balance Therapy With Hands-Free Mobile Robotic Feedback for At-Home Training Across the Lifespan - Ava D. Segal; Peter G. Adamczyk; Andrew J. Petruska; Anne K. Silverman (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2022)
Providing aging adults with engaging, at-home balance therapy is essential to promote long-term adherence to unsupervised training and to foster independence. We developed a portable interactive balance training system that provides real-world visual cues on balance performance using wobble board tilt angles to control the speed of a robotic car platform in a three-dimensional environment. The goal of this study was to validate this mobile balance therapy system for home use across the lifespan. Twenty younger (18-39 years) and nineteen older (58-74 years) healthy adults performed balance training with and without visual feedback while standing on a wobble board instrumented with a consumer-grade inertial measurement unit (IMU) and optical motion tracking markers. Participants performed feedback trials based on either the robotic car’s movements or a commercially-available virtual game. Wobble board tilt measurements were highly correlated between IMU and optical measurement systems ( $\text {R}{>}{0.84}$ ), with high agreement in outcome metrics ( $\text {ICC}{>}{0.99}$ ) and small bias ( $\text {mean}{ < }{3}%$ ). Both measurement systems identified similar aging, feedback, and stance type effects including (1) altered movement control when older adults performed tilting trials with either robotic or virtual feedback compared to without feedback, (2) two-fold greater wobble board oscillations in older vs. younger adults during steady standing, (3) no difference in board oscillations during steady standing in narrow vs. wide double support, and (4) greater wobble board oscillations for single compared to double support. These findings demonstrate the feasibility of implementing goal-directed robotic balance training with mobile tracking of balance performance in home environments.